The photodynamic therapeutic activities and optical limiting properties of metalated asymmetric porphyrins and corroles - Burgess, Kristen Paige (Rhodes University, Faculty of Science, Department of Chemistry)
Cancer is a devastating disease that is a leading cause of death worldwide. Despite the available cancer treatments, there is a significant need to improve the therapeutic approach towards this disease. Photodynamic therapy (PDT) is an alternative approach for treating cancer, which requires a photosensitiser, molecular oxygen and light. Although some porphyrin-based derivatives have been approved by the United States Food and Drug Administration (FDA) and other similar agencies elsewhere for photodynamic therapy, their relatively poor photophysicochemical properties mean that there is an ongoing need for new photosensitiser dyes. Singlet oxygen photosensitiser dyes can also be used to treat bacteria that develop antimicrobial resistance in the context of photodynamic antimicrobial chemotherapy (PACT). The main aim of this study was to synthesise and characterise a series of porphyrin dyes with 4-quinolinyl, thien-2-yl and 4-bromo-thien-2-yl meso-aryl groups and their Sn(IV) and In(III) complexes, as well as their corrole analogues. Corroles are contracted macrocycles that have interesting optical properties. The corroles selected for study were found to be difficult to synthesise and purify and had unfavourable photophysicochemical properties and were thus omitted from the PDT and PACT biological applications within this thesis. High- and low-symmetry A4 and ABAB type meso-tetraarylporphyrins porphyrins were synthesised to improve the photophysicochemical properties of the photosensitisers; the utility of these dyes as photosensitisers was studied against the MCF-7 breast cancer cell line for PDT and against Staphylococcus aureus and Escherichia coli for PACT. The thienyl-2-yl rings were introduced to red shift the lowest energy Q band towards the phototherapeutic window, while quaternisation of the nitrogen and sulfur atoms of the 4-quinolinyl and thien-2-yl rings to introduce a cationic nature was explored to improve the bioavailability of the drugs and uptake into the target cell walls for improved efficacy. Heavy Sn(IV) and In(III) central metal ions were introduced to enhance the singlet oxygen quantum yields and limit aggregation through axial ligation. The bromine atoms of the 4-bromo-thien-2-yl meso-aryl rings were also introduced to enhance the singlet oxygen quantum yields of the dyes. Furthermore, the utility of the porphyrin and corrole molecules for optical limiting properties to limit laser radiation to protect optical devices, including eyes, was explored by the z-scan technique. One of the dyes studied, Sn(IV) tetrathien-2-ylporphyrin, that exhibited the most favourable reverse saturable absorbance (RSA) response was embedded into a poly(bisphenol carbonate A) polymer thin film to further explore its suitability for practical applications.
Keywords: Porphyrins; Corrole; Photochemotherapy; Anti-infective agents; Nonlinear optics; Z-scan technique; Active oxygen; Time-dependent density functional theory; Chemical synthesis